High-energy-storage flexible wood fiber board as well as preparation method and application thereof
By introducing non-isocyanate polyurethane formed by the reaction of epoxy soybean oil ring carbonate and soy protein in the wood fiberboard, combining acrylamide and conductive materials, using multi-dimensional-multi-scale hierarchical directional composite assembly technology, high-energy storage flexible wood was prepared by using multi-dimensional and multi-scale hierarchical directional composite assembly technology. Fiberboard solves the problems of high energy consumption and complex functionalization of wood materials in the prior art, and realizes efficient high-value utilization and functionalization.
Patent Information
- Application Number
- CN202411384844.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The modification of existing wood materials requires a large amount of organic chemical reagents and energy, and the deconstruction and recombination methods of wood materials from the molecular level are too complex, resulting in its loss of its intrinsic characteristics, making it difficult to achieve high-value utilization and functionalization of wood materials. .
By mixing epoxy soybean oil with tetrabutyl ammonium bromide, reacting with carbon dioxide with heating and pressure, epoxy soybean oil ring carbonate is obtained, and reacting with soy protein to form bio-based aqueous non-isocyanate polyurethane, combining acrylamide and conductive materials , adopt multi-dimensional-multi-scale hierarchical directional composite assembly technology to prepare high-energy storage flexible wood fiberboard.
It has achieved the preparation of high-energy storage flexible wood fiberboard, with high specific capacitance (31.57mF) and good mechanical properties, can withstand 40% of its own strain without breaking, and the maximum tensile stress reaches 1.7MPa, suitable for smart furniture. The application of wood materials has promoted the high-value utilization.
Smart Images

Figure CN119458555A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wood functional materials, and in particular relates to a high-energy storage flexible wood fiberboard and a preparation method and application thereof. Background Art
[0002] Wood materials are a sustainable, renewable, biodegradable and environmentally friendly material that exists in large quantities in nature. At the same time, due to their advantages such as light weight, high strength and easy processing, they have been widely used in building support, interior decoration, packaging, pulp and paper making, and biomass energy.
[0003] At present, wood materials are mainly prepared into three types of wood-based panels (plywood, particleboard, and fiberboard). Due to the characteristics of high raw material utilization, low production cost, and stable performance, wood-based panels are mainly used in the manufacture of traditional furniture such as bookcases, sofas, and door panels. However, this also leads to problems such as single product function, low high-value utilization, and overcapacity at the low end in the utilization of wood materials. As an important means to improve the quality of wood and increase the added value of wood materials, the functionalization of wood materials can break the limitations of wood materials in practical applications. In recent years, researchers have proposed a variety of functionalization methods for wood materials, mainly including: (i) using chemical and physical treatment methods to structurally transform wood materials through component removal, pore modification, and high-temperature carbonization; (ii) using the multi-scale hierarchical structure of wood materials, starting from the molecular perspective of wood materials, to construct functionalized materials through self-assembly, directional arrangement, or aggregation molding.
[0004] At present, the above research has made some progress, but there are still two major defects: on the one hand, the modification of wood materials requires a large amount of organic chemical reagents and energy, which limits the further large-scale utilization of functional wood materials; on the other hand, the deconstruction and reconstruction of wood materials at the molecular level are too complicated, and at the same time, they will lose some excellent intrinsic properties. Therefore, how to achieve the intrinsic functionalization of wood materials through simple and green means is of great significance to broaden the application scope of wood materials, improve the quality of wood material products, and promote the large-scale application of functional wood materials.
[0005] With the rapid development of the Internet of Things and artificial intelligence technologies, smart homes that enable human-computer interaction are playing an increasingly important role in improving people's quality of life and health. At present, smart homes are developing in a more intelligent and interconnected direction, using artificial intelligence technology to intelligently perceive, analyze and adapt to users' habits and needs, and provide more personalized and intelligent home services. In addition, the interconnection between smart home devices will be more seamless and efficient, and a higher level of automation and collaboration will be achieved through sharing information and data. However, the intelligence and interconnection of smart homes rely more on integrating intelligent systems that can receive, process and execute user requirements into furniture to achieve the requirements of smart home integration, which is something that traditional furniture with only a single carrier function cannot meet.
[0006] Therefore, it is urgent to make the furniture material multifunctional by giving it the intrinsic energy storage property to meet the development requirements of smart homes. Summary of the invention
[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0009] Therefore, the object of the present invention is to overcome the deficiencies of the prior art and provide a method for preparing a high energy storage flexible wood fiberboard.
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a high energy storage flexible wood fiberboard, comprising:
[0011] The epoxy soybean oil is mixed with tetrabutylammonium bromide, and the mixture is heated and pressurized to react with carbon dioxide to obtain the epoxy soybean oil cyclocarbonate;
[0012] The soy protein powder is mixed with distilled water to obtain a mixed solution, and the mixed solution is subjected to a heating treatment to obtain a soy protein water dispersion;
[0013] Epoxidized soybean oil-based cyclic carbonate is added to a soybean protein aqueous dispersion, the pH is adjusted to 10, and the mixture is heated for reaction to obtain a bio-based water-based non-isocyanate polyurethane;
[0014] acrylamide and lithium chloride are added into the bio-based water-based non-isocyanate polyurethane, and fully dissolved to obtain a non-isocyanate polyurethane-acrylamide prepolymer;
[0015] The conductive material is doped into the wood fiber and fully stirred to make it evenly dispersed to obtain a wood fiber mixture;
[0016] The non-isocyanate polyurethane-acrylamide prepolymer is uniformly sprayed on the wood fiber mixture, and after being uniformly stirred, the sizing wood fiber is obtained;
[0017] After N,N'-methylenebisacrylamide and ammonium persulfate are sprayed on the glued wood fiber, the fiber is pre-pressed in a mold, and then hot-pressed on a flat vulcanizer to cure and cross-link to obtain a high-energy storage flexible wood fiberboard.
[0018] As a preferred embodiment of the preparation method of the present invention, the epoxy soybean oil and tetrabutylammonium bromide are mixed, wherein the mass ratio of the epoxy soybean oil to the tetrabutylammonium bromide is 1:0.01; and the heating and pressurization are reacted with carbon dioxide, wherein the heating temperature is 130° C. and the pressure is 2.5 MPa.
[0019] As a preferred embodiment of the preparation method of the present invention, the soy protein powder is mixed with distilled water to obtain a mixed liquid, wherein the concentration of the soy protein in the mixed liquid is 0.13-0.15 g / mL; the heating treatment obtains a soy protein water dispersion, wherein the heating temperature is 90-95°C and the heating stirring time is 1.5-2h.
[0020] As a preferred embodiment of the preparation method of the present invention, the epoxy soybean oil-based cyclic carbonate is added to the soybean protein aqueous dispersion, wherein the mass ratio of the epoxy soybean oil-based cyclic carbonate to the soybean protein aqueous dispersion is 1:3.3 to 1:3.5.
[0021] As a preferred embodiment of the preparation method of the present invention, the heating reaction obtains a bio-based water-based non-isocyanate polyurethane, wherein the heating temperature is 80-85° C. and the reaction time is 0.5-1 h.
[0022] As a preferred embodiment of the preparation method of the present invention, acrylamide and lithium chloride are added to the bio-based water-based non-isocyanate polyurethane, wherein the mass ratio of acrylamide to the bio-based water-based non-isocyanate polyurethane is 1:0.85 to 1:0.87, and the mass ratio of lithium chloride to the bio-based water-based non-isocyanate polyurethane is 1:75 to 1:77.
[0023] As a preferred embodiment of the preparation method of the present invention, the mass ratio of the conductive material to the wood fiber is 1:2;
[0024] The mass ratio of the non-isocyanate polyurethane-acrylamide prepolymer to the wood fiber is 1:1.
[0025] As a preferred embodiment of the preparation method of the present invention, the amount of N,N'-methylenebisacrylamide added is 0.10-0.13% of the mass of acrylamide, and the amount of ammonium persulfate added is 4-5% of the mass of acrylamide;
[0026] The hot pressing temperature is 60° C., the pressure is 0.4 MPa, and the hot pressing time is 3 hours.
[0027] Another object of the present invention is to overcome the shortcomings of the prior art and to provide a method for preparing a high energy storage flexible wood fiberboard, wherein: the high energy storage flexible wood fiberboard has a specific capacitance of 31.57mF, can withstand 40% of its own strain without breaking, and has a maximum tensile stress of 1.7MPa.
[0028] Another object of the present invention is to overcome the deficiencies of the prior art and provide a high energy storage flexible wood fiberboard for use in smart furniture.
[0029] Beneficial effects of the present invention:
[0030] (1) The present invention provides a method for preparing a high-energy storage flexible wood fiber board and its application. First, a new conductive adhesive is prepared, and a non-isocyanate polyurethane formed by the reaction of epoxidized soybean oil cyclic carbonate and soybean protein is dispersed in the entanglement chain of polyacrylamide macromolecules. The hydrogen bonding between the entanglement chain of polyacrylamide and the non-isocyanate polyurethane is used to transfer external stress and dissipate energy, thereby improving the toughness of the adhesive. At the same time, a three-dimensional network structure formed by mixing porous wood fiber materials is used to introduce conductive materials to prepare conductive composite wood fibers. The multi-dimensional-multi-scale hierarchical directional composite assembly technology of wood fiber materials and the new conductive adhesive is used to achieve directional transmission of charges from polymers to wood pores, so that the flexible wood fiber board has the characteristic of intrinsic high energy storage.
[0031] (2) The present invention uses a new type of high-conductivity adhesive to prepare a high-energy storage flexible wood fiberboard, which helps to solve the problem of the single carrier function of traditional furniture, provides a new idea for the realization of IoT-integrated smart sustainable home, and helps to promote the high-value utilization of wood materials.
[0032] (3) The preparation process of the present invention is simple, does not use organic solvents, has low energy consumption, is easy to produce in large quantities, and is conducive to industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0034] Figure 1 3 is a microscopic morphology image of the non-isocyanate polyurethane-polyacrylamide conductive adhesive in Example 2 of the present invention; wherein a is a transmission electron microscope image of the non-isocyanate polyurethane, and b is a scanning electron microscope image of the non-isocyanate polyurethane-polyacrylamide conductive adhesive.
[0035] Figure 2 : is a toughness diagram of the soy protein-epoxidized soybean oil-based cyclocarbonate-polyacrylamide bio-based gel adhesive in an embodiment of the present invention; wherein, a is a stress-strain curve diagram of the polymer gel, bd is a tear energy diagram of the bio-based gel adhesive, and e is a comparison diagram of Young's modulus, fracture stress, fracture strain and tear energy of the bio-based gel adhesives of different embodiments.
[0036] Figure 3 1 is the stress-strain curve of a single stretching-releasing cycle under different strains of the soy protein-epoxidized soybean oil-based cyclocarbonate-polyacrylamide bio-based gel adhesive in an embodiment of the present invention.
[0037] Figure 4 This is a diagram of the electrochemical performance of a flexible wood fiberboard with high energy storage in an embodiment of the present invention.
[0038] Figure 5 1 is a stress-strain curve of a single stretch-release cycle under different strains of a high energy storage flexible wood fiberboard in an embodiment of the present invention.
[0039] Figure 6 This is an application diagram of the high energy storage flexible wood fiberboard in Example 6 of the present invention.
[0040] Figure 7 It is a comparison diagram of the mechanical properties of the soy protein-epoxidized soybean oil-based cyclocarbonate-polyacrylamide bio-based gel adhesive prepared in Comparative Examples 1 and 2 of the present invention and Example 2; wherein a and b are tear energy diagrams of the bio-based gel adhesive, c is a stress-strain curve of a single stretch-release cycle under different strains, and d is a comparison diagram of Young's modulus, fracture stress, fracture strain and tear energy of the conductive adhesives of different embodiments.
[0041] Figure 8 This is a single stretch-release cycle test diagram of the flexible wood fiberboard prepared in Comparative Example 3 and Example 6 of the present invention under different strains. DETAILED DESCRIPTION
[0042] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0044] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0045] The invention comprises the following ingredients: soybean protein isolate: MacLean reagent; epoxidized soybean oil: Aladdin reagent; tetrabutylammonium bromide: Aladdin reagent; acrylamide: Aladdin reagent; ammonium persulfate: Sigma-Aldrich reagent; N,N'-methylenebisacrylamide: Sigma-Aldrich reagent; aniline: MacLean reagent; hydrochloric acid: Nanjing Chemical Reagent; and conductive activated carbon: Xianfeng Nano Reagent.
[0046] Example 1
[0047] This embodiment provides a method for preparing a non-isocyanate polyurethane-polyacrylamide conductive adhesive by polymerization, the main steps of which are:
[0048] (1) 1000 g of epoxidized soybean oil and 10 g of tetrabutylammonium bromide were added to a 2 L autoclave, and carbon dioxide was continuously introduced to evacuate the air in the autoclave, and the pressure in the autoclave was maintained at 2.5 MPa;
[0049] The reaction was stirred at 130°C in a carbon dioxide environment for 48 hours to obtain a golden viscous epoxy soybean oil cyclic carbonate;
[0050] (2) Disperse 20 g of soy protein isolate powder in 150 mL of deionized water and stir at room temperature for 0.5 h to allow it to be fully soaked;
[0051] (3) Add 3 g of epoxy soybean oil-based cyclic carbonate to 10 g of soy protein isolate aqueous dispersion, and gradually add sodium hydroxide solution dropwise while stirring until the pH is 10;
[0052] The reaction was carried out at 85°C for 1 h to obtain a bio-based water-based non-isocyanate polyurethane;
[0053] (4) adding 15 g of acrylamide monomer and 0.17 g of lithium chloride to the non-isocyanate polyurethane-acrylamide prepolymer cooled to room temperature, stirring at 55° C. for 0.5 h to fully dissolve the monomer, thereby forming a non-isocyanate polyurethane-acrylamide prepolymer;
[0054] (5) 0.1 mmol N,N'-methylenebisacrylamide and 0.08 mmol ammonium persulfate were added dropwise to the non-isocyanate polyurethane-acrylamide prepolymer and stirred at room temperature for 15 minutes to fully dissolve the prepolymer;
[0055] (6) The non-isocyanate polyurethane-acrylamide prepolymer was poured into a square glass mold with a length of 12 cm and a thickness of 0.2 cm and polymerized at 35° C. for 3 h to obtain a non-isocyanate polyurethane-acrylamide conductive adhesive.
[0056] Example 2
[0057] This embodiment provides a method for preparing a non-isocyanate polyurethane-polyacrylamide conductive adhesive by polymerization, the main steps of which are:
[0058] (1) 1000 g of epoxidized soybean oil and 10 g of tetrabutylammonium bromide were added to a 2 L autoclave, and carbon dioxide was continuously introduced to evacuate the air in the autoclave, and the pressure in the autoclave was maintained at 2.5 MPa;
[0059] The reaction was stirred at 130°C in a carbon dioxide environment for 48 hours to obtain a golden viscous epoxy soybean oil cyclic carbonate;
[0060] (2) Disperse 20 g of soy protein isolate powder in 150 mL of deionized water and stir at room temperature for 0.5 h to allow it to be fully soaked;
[0061] (3) Add 3 g of epoxy soybean oil-based cyclic carbonate to 10 g of soy protein isolate aqueous dispersion, and gradually add sodium hydroxide solution dropwise while stirring until the pH is 10;
[0062] The reaction was carried out at 85°C for 1 h to obtain a bio-based water-based non-isocyanate polyurethane;
[0063] (4) adding 15 g of acrylamide monomer and 0.51 g of lithium chloride to the non-isocyanate polyurethane-acrylamide prepolymer cooled to room temperature, stirring at 55° C. for 0.5 h to fully dissolve the monomer, thereby forming a non-isocyanate polyurethane-acrylamide prepolymer;
[0064] (5) 0.1 mmol N,N'-methylenebisacrylamide and 0.08 mmol ammonium persulfate were added dropwise to the non-isocyanate polyurethane-acrylamide prepolymer and stirred at room temperature for 15 minutes to fully dissolve the prepolymer;
[0065] (6) The non-isocyanate polyurethane-acrylamide prepolymer was poured into a square glass mold with a length of 12 cm and a thickness of 0.2 cm and polymerized at 35° C. for 3 h to obtain a non-isocyanate polyurethane-acrylamide conductive adhesive.
[0066] Example 3
[0067] This embodiment provides a method for preparing a non-isocyanate polyurethane-polyacrylamide conductive adhesive by polymerization, the main steps of which are:
[0068] (1) 1000 g of epoxidized soybean oil and 10 g of tetrabutylammonium bromide were added to a 2 L autoclave, and carbon dioxide was continuously introduced to evacuate the air in the autoclave, and the pressure in the autoclave was maintained at 2.5 MPa;
[0069] The reaction was stirred at 130°C in a carbon dioxide environment for 48 hours to obtain a golden viscous epoxy soybean oil cyclic carbonate;
[0070] (2) Disperse 20 g of soy protein isolate powder in 150 mL of deionized water and stir at room temperature for 0.5 h to allow it to be fully soaked;
[0071] (3) Add 3 g of epoxy soybean oil-based cyclic carbonate to 10 g of soy protein isolate aqueous dispersion, and gradually add sodium hydroxide solution dropwise while stirring until the pH is 10;
[0072] The reaction was carried out at 85°C for 1 h to obtain a bio-based water-based non-isocyanate polyurethane;
[0073] (4) adding 15 g of acrylamide monomer and 0.85 g of lithium chloride to the non-isocyanate polyurethane-acrylamide prepolymer cooled to room temperature, stirring at 55° C. for 0.5 h to fully dissolve the monomer, thereby forming a non-isocyanate polyurethane-acrylamide prepolymer;
[0074] (5) 0.1 mmol N,N'-methylenebisacrylamide and 0.08 mmol ammonium persulfate were added dropwise to the non-isocyanate polyurethane-acrylamide prepolymer and stirred at room temperature for 15 minutes to fully dissolve the prepolymer;
[0075] (6) The non-isocyanate polyurethane-acrylamide prepolymer was poured into a square glass mold with a length of 12 cm and a thickness of 0.2 cm and polymerized at 35° C. for 3 h to obtain a non-isocyanate polyurethane-acrylamide conductive adhesive.
[0076] The microstructure of gel adhesives Figure 1As shown in the figure, the SEM photo shows that the adhesive presents a chain entanglement network structure, in which the spherical non-isocyanate polyurethane generated by the epoxy soybean oil cyclocarbonate and soybean protein nanoparticles is evenly dispersed in the skeleton structure, serving as an entanglement site to form a high degree of chain entanglement in the polyacrylamide macromolecular chain. The non-isocyanate polyurethane clusters generated by the reaction of epoxy soybean oil-based cyclocarbonate and soybean protein are spherical, while polyacrylamide is a continuous phase, and the spherical agglomerates formed by the non-isocyanate polyurethane are dispersed in the continuous phase.
[0077] Example 4
[0078] This embodiment provides a method for preparing a high energy storage flexible wood fiberboard, the main steps of which are:
[0079] (1) 0.8 g of activated carbon and 0.2 g of single-walled carbon nanotube powder were mixed and ground for 0.5 h, and then stirred with 2 g of wood fiber for 10 min to make them evenly dispersed in the wood fiber;
[0080] (2) 3 g of the non-isocyanate polyurethane-acrylamide prepolymer prepared in Example 2 was evenly sprayed on the wood fiber, and mechanically stirred to obtain sizing wood fiber;
[0081] (3) Spray 0.1 mmol N,N'-methylenebisacrylamide and 0.027 mol ammonium persulfate solution onto the glued wood fiber and stir for 5 min to fully infiltrate it;
[0082] (4) The glued wood fibers are pre-pressed into shape in a mold, and then hot-pressed on a flat vulcanizer (60°C, pressure 0.4 MPa, hot-pressing time 3 h) to obtain a high energy storage flexible wood fiberboard through curing and cross-linking.
[0083] Example 5
[0084] This embodiment provides a method for preparing a high energy storage flexible wood fiberboard, the main steps of which are:
[0085] (1) Add 0.365 mL of aniline to 15 mL of 1 M dilute hydrochloric acid and stir for 15 min to form an aniline emulsion;
[0086] (2) Dissolve 0.228 g of ammonium persulfate in 5 mL of 1 M dilute hydrochloric acid and stir for 15 min to form an ammonium persulfate solution;
[0087] (3) slowly stirring the aniline emulsion into an ammonium persulfate solution in an ice bath, and allowing it to polymerize for 6 hours to obtain a dark green liquid;
[0088] (4) Filter the dark green liquid and wash it with deionized water and anhydrous ethanol;
[0089] The filtered solid was dried at 60°C for 12 h to obtain dark green polyaniline particles;
[0090] (5) 0.5 g of activated carbon and 0.5 g of polyaniline were mixed and ground for 0.5 h, and then stirred with 2 g of wood fiber for 10 min to fully disperse them in the wood fiber;
[0091] (6) 3 g of the non-isocyanate polyurethane-acrylamide prepolymer prepared in Example 2 is evenly sprayed on the wood fiber, and mechanically stirred to obtain sizing wood fiber;
[0092] (7) Spray 0.1 mmol N,N'-methylenebisacrylamide and 0.027 mol ammonium persulfate solution onto the glued wood fiber and stir for 5 min to fully soak it;
[0093] (8) The glued wood fibers are pre-pressed into shape in a mold, and then hot-pressed on a flat vulcanizer (60°C, pressure 0.4 MPa, hot-pressing time 3 h) to obtain a high energy storage flexible wood fiberboard through curing and cross-linking.
[0094] Example 6
[0095] This embodiment provides a method for preparing a flexible wood fiberboard with high energy storage, the main steps of which are:
[0096] (1) Add 0.365 mL of aniline to 15 mL of 1 M dilute hydrochloric acid and stir for 15 min to form an aniline emulsion;
[0097] (2) Dissolve 0.228 g of ammonium persulfate in 5 mL of 1 M dilute hydrochloric acid and stir for 15 min to form an ammonium persulfate solution;
[0098] Dissolve 0.1g activated carbon in ammonium persulfate solution and stir for 20min to fully soak it;
[0099] (3) slowly adding the aniline emulsion to the ammonium persulfate solution in an ice bath with stirring, and stirring and polymerizing for 6 hours to obtain a dark green liquid;
[0100] (4) Filter the dark green liquid and wash it with deionized water and anhydrous ethanol;
[0101] The filtered solid was dried at 60°C for 12 h to obtain dark red activated carbon in-situ polymerized polyaniline particles;
[0102] (5) 1 g of activated carbon in-situ polymerized polyaniline particles was mixed and ground for 0.5 h, and then stirred with 2 g of wood fiber for 10 min to fully disperse it in the wood fiber;
[0103] (6) 3 g of the non-isocyanate polyurethane-acrylamide prepolymer prepared in Example 2 is evenly sprayed on the wood fiber, and mechanically stirred to obtain sizing wood fiber;
[0104] (7) Spray 0.1 mmol N,N'-methylenebisacrylamide and 0.027 mol ammonium persulfate solution onto the glued wood fiber and stir for 5 min to fully soak it;
[0105] (8) The glued wood fibers are pre-pressed into shape in a mold, and then hot-pressed on a flat vulcanizer (60°C, pressure 0.4 MPa, hot-pressing time 3 h) to obtain a high energy storage flexible wood fiberboard through curing and cross-linking.
[0106] Example 7
[0107] Mechanical properties analysis of non-isocyanate polyurethane-polyacrylamide conductive adhesive:
[0108] The mechanical properties of non-isocyanate polyurethane-polyacrylamide conductive adhesives were evaluated by analyzing the tensile properties and fatigue strength of the samples.
[0109] The non-isocyanate polyurethane-polyacrylamide conductive adhesives prepared in the above Examples 1, 2 and 3 were cut into dumbbell-shaped non-notched samples (stretched length of 20 mm, width of 4 mm, thickness of 2 mm) and notched samples (stretched length of 20 mm, width of 4 mm, thickness of 2 mm, notch width = 2 mm), respectively; then, an electronic universal testing machine with a load of 1 kN was used to perform a uniaxial tensile test and a single stretch-release cycle test under different strains on the samples in the vertical direction to obtain a stretch-strain curve and an energy dissipation diagram, and thereby obtain the tear energy, tensile fracture stress and fracture strain of the samples.
[0110] The tensile tests were carried out at room temperature with a tensile rate of 50 mm / min.
[0111] The test results are as follows Figure 2 , 3 By comparing Examples 1, 2, and 3, it can be seen that with the increase of lithium chloride, the elongation at break increases from 379% to 466% and then decreases to 344%, and the tensile stress increases from 668 kPa to 1813 kPa and then decreases to 723 kPa. The Young's modulus and tear energy of Examples 1, 2, and 3 are further compared. The gel adhesive prepared in Example 2 reaches 1.1 MPa and 17.31 kJ m -2 .
[0112] At the same time, the maximum stress that can be sustained by a single stretch-release under different strains in Example 2 is much higher than that in Example 1 and Example 3. This shows that the introduction of an appropriate amount of salt ions can improve the toughness of the adhesive.
[0113] Example 8
[0114] Electrochemical performance test of non-isocyanate polyurethane-polyacrylamide conductive adhesive:
[0115] The conductivity mechanical properties of the non-isocyanate polyurethane-polyacrylamide conductive adhesive were tested using an electrochemical workstation. The non-isocyanate polyurethane-polyacrylamide conductive adhesives prepared in the above Examples 1, 2, and 3 were cut into rectangular samples with a length of 10 mm, a width of 10 mm, and a thickness of 2 mm to prepare platinum sheet | conductive adhesive | platinum sheet capacitors. The ionic conductivity of the conductive adhesive was tested using electrochemical impedance spectroscopy.
[0116] As shown in Table 1, it can be seen from the non-isocyanate polyurethane-polyacrylamide conductive adhesives in Examples 1-3 that the introduction of lithium chloride improves the electrochemical performance of the adhesive.
[0117] Table 1
[0118] <![CDATA[Ionic conductivity / mScm -1 > Example 1 35.82 Example 2 38.67 Example 3 36.48
[0119] Example 9
[0120] Analysis of electrochemical performance of high energy storage flexible wood fiberboard:
[0121] The electrochemical performance of the high energy storage flexible wood fiberboard was evaluated by analyzing the constant current charge and discharge tests of the samples.
[0122] An electrochemical workstation was used to perform constant current charge and discharge tests on the high energy storage flexible wood fiberboard under different current conditions of 0.0005-0.125 mA in a voltage window of 0-1 V. The high energy storage flexible wood fiberboards prepared in the above-mentioned Examples 4, 5, and 6 were cut into cube samples with a length of 2 cm, a width of 2 cm, and a thickness of 1.5 mm to prepare single-walled carbon nanotube paper | wood fiberboard | single-walled carbon nanotube paper devices to test the electrochemical properties of the high energy storage flexible wood fiberboards.
[0123] like Figure 4 As shown, compared with Examples 4 and 5, Example 6 can withstand a larger current density (0.05 mA cm -2 ) and has higher specific capacitance (31.57mF) and energy density (7.18mWh m -2 ), the Coulombic efficiency reached 92.90%. -2 Increase to 0.5 mA cm -2 When , the specific capacitance of Example 6 can still be maintained at 18.67 mF, and the Coulomb efficiency is above 80%.
[0124] This shows that the wood fiberboard prepared by introducing activated carbon of in situ polymerized polyaniline into wood fibers and through a multi-scale and multi-dimensional directional assembly strategy has excellent electrical storage properties.
[0125] Example 10
[0126] Analysis of mechanical properties of high energy storage flexible wood fiberboard:
[0127] The mechanical properties of high energy storage flexible wood fiberboard were evaluated by analyzing single stretch-release cycle experiments at different strains of the samples.
[0128] The high energy storage flexible wood fiberboard prepared in the above Example 6 was cut into rectangular samples (stretching length of 50 mm, width of 4 mm, thickness of 1.5 mm), and then a single stretching-releasing cycle experiment under different strains was performed on the sample along the vertical direction using an electronic universal testing machine with a load of 1 kN to obtain a stretching-strain curve graph.
[0129] The results are as follows Figure 5 As shown, the high energy storage flexible fiberboard prepared in Example 6 can withstand 40% of its own strain without breaking, and the maximum tensile stress reaches 1.7 MPa, showing a certain flexibility.
[0130] Embodiment 11
[0131] Application demonstration of high energy storage flexible wood fiberboard:
[0132] The high energy storage flexible wood fiberboard prepared in the above Example 6 was cut into square samples (length 70 mm, thickness 1.5 mm), and single-walled carbon nanotube paper was used as the current collector to prepare a single-walled carbon nanotube paper | wood fiberboard | single-walled carbon nanotube paper device. The high energy storage flexible wood fiberboard was charged for 30 minutes using an electrochemical workstation at a voltage window of 0 to 5 V and a current of 2.5 mA, and then power was provided for the timer.
[0133] The results are as follows Figure 6 As shown, the high energy storage flexible fiberboard can maintain the stable operation of the timer even after folding, twisting, hammering and shearing; this shows that the prepared wood fiberboard not only has good energy storage performance, but also has excellent flexibility; at the same time, even under harsh conditions, the prepared high energy storage flexible wood fiberboard can still work normally and stably.
[0134] Comparative Example 1
[0135] This embodiment provides a method for preparing a non-isocyanate polyurethane-polyacrylamide conductive adhesive, the main steps of which are:
[0136] (1) 1000 g of epoxidized soybean oil and 10 g of tetrabutylammonium bromide were added to a 2 L autoclave, and carbon dioxide was continuously introduced to evacuate the air in the autoclave, and the pressure in the autoclave was maintained at 2.5 MPa;
[0137] The reaction was stirred at 130°C in a carbon dioxide environment for 48 hours to obtain a golden viscous epoxy soybean oil cyclic carbonate;
[0138] (2) Disperse 20 g of soy protein isolate powder in 150 mL of deionized water and stir at room temperature for 0.5 h to allow it to be fully soaked;
[0139] (3) Add 3 g of epoxy soybean oil-based cyclic carbonate to 10 g of soy protein isolate aqueous dispersion, and gradually add sodium hydroxide solution dropwise while stirring until the pH is 10;
[0140] The reaction was carried out at 85°C for 1 h to obtain a bio-based water-based non-isocyanate polyurethane;
[0141] (4) adding 15 g of acrylamide monomer and 0.51 g of lithium chloride to the non-isocyanate polyurethane-acrylamide prepolymer cooled to room temperature, stirring at 55° C. for 0.5 h to fully dissolve the monomer, thereby forming a non-isocyanate polyurethane-acrylamide prepolymer;
[0142] (5) 0.1 mmol N,N'-methylenebisacrylamide and 0.12 mmol ammonium persulfate were added dropwise to the non-isocyanate polyurethane-acrylamide prepolymer and stirred at room temperature for 15 minutes to fully dissolve the prepolymer;
[0143] (6) The non-isocyanate polyurethane-acrylamide prepolymer was poured into a square glass mold with a length of 12 cm and a thickness of 0.2 cm and polymerized at 35° C. for 3 h to obtain a non-isocyanate polyurethane-acrylamide conductive adhesive.
[0144] Comparative Example 2
[0145] (1) 1000 g of epoxidized soybean oil and 10 g of tetrabutylammonium bromide were added to a 2 L autoclave, and carbon dioxide was continuously introduced to evacuate the air in the autoclave, and the pressure in the autoclave was maintained at 2.5 MPa;
[0146] The reaction was stirred at 130°C in a carbon dioxide environment for 48 hours to obtain a golden viscous epoxy soybean oil cyclic carbonate;
[0147] (2) Disperse 20 g of soy protein isolate powder in 150 mL of deionized water and stir at room temperature for 0.5 h to allow it to be fully soaked;
[0148] (3) Add 3 g of epoxy soybean oil-based cyclic carbonate to 10 g of soy protein isolate aqueous dispersion, and gradually add sodium hydroxide solution dropwise while stirring until the pH is 10;
[0149] The reaction was carried out at 85°C for 1 h to obtain a bio-based water-based non-isocyanate polyurethane;
[0150] (4) adding 15 g of acrylamide monomer and 0.51 g of lithium chloride to the non-isocyanate polyurethane-acrylamide prepolymer cooled to room temperature, stirring at 55° C. for 0.5 h to fully dissolve the monomer, thereby forming a non-isocyanate polyurethane-acrylamide prepolymer;
[0151] (5) 0.1 mmol N,N'-methylenebisacrylamide and 0.04 mmol ammonium persulfate were added dropwise to the non-isocyanate polyurethane-acrylamide prepolymer and stirred at room temperature for 15 minutes to fully dissolve the prepolymer;
[0152] (6) The non-isocyanate polyurethane-acrylamide prepolymer was poured into a square glass mold with a length of 12 cm and a thickness of 0.2 cm and polymerized at 35° C. for 3 h to obtain a non-isocyanate polyurethane-acrylamide conductive adhesive.
[0153] The non-isocyanate polyurethane-polyacrylamide conductive adhesive prepared in the above comparative examples 1 and 2 was cut into non-notched samples (stretched length of 20 mm, width of 4 mm, thickness of 2 mm) and notched samples (stretched length of 20 mm, width of 4 mm, thickness of 2 mm, notch width = 2 mm); then the non-notched and notched samples were subjected to tensile fracture tests using an electronic universal testing machine with a load of 1 kN to obtain a tension-displacement curve with a tensile rate of 50 mm / min. The covering area was determined based on the non-notched tension and the displacement at which the notch crack began to expand, and the tearing energy was calculated.
[0154] The test results are as follows Figure 7 By comparing Examples 1 and 2 with Example 2, it can be seen that when the mass ratio of ammonium persulfate to acrylamide is not properly controlled, the Young's modulus, fracture stress and tear energy of the prepared conductive adhesive are significantly reduced compared with those of Example 2, and the toughness difference is large.
[0155] The non-isocyanate polyurethane-polyacrylamide conductive adhesives prepared in Comparative Examples 1 and 2 were subjected to a single stretch-release cycle test under different strains and compared with Example 2. The results are as follows: Figure 7 As shown in c. It can be seen that when the mass ratio of ammonium persulfate to acrylamide is not properly controlled, the maximum cyclic tensile stress of the prepared gel adhesive in a single stretch-release cycle under different strains is reduced by 28.62% and 91.00% respectively compared with Example 2, reflecting poor toughness.
[0156] Comparative Example 3
[0157] (1) Add 0.365 mL of aniline to 15 mL of 1 M dilute hydrochloric acid and stir for 15 min to form an aniline emulsion;
[0158] (2) Dissolve 0.228 g of ammonium persulfate in 5 mL of 1 M dilute hydrochloric acid and stir for 15 min to form an ammonium persulfate solution;
[0159] Dissolve 0.1g activated carbon in ammonium persulfate solution and stir for 20min to fully soak it;
[0160] (3) slowly adding the aniline emulsion to the ammonium persulfate solution in an ice bath with stirring, and stirring and polymerizing for 6 hours to obtain a dark green liquid;
[0161] (4) Filter the dark green liquid and wash it with deionized water and anhydrous ethanol;
[0162] The filtered solid was dried at 60°C for 12 h to obtain dark red activated carbon in-situ polymerized polyaniline particles;
[0163] (5) 1 g of activated carbon in-situ polymerized polyaniline particles was mixed and ground for 0.5 h, and then stirred with 2 g of wood fiber for 10 min to fully disperse it in the wood fiber;
[0164] (6) 3 g of acrylamide prepolymer (15 g of acrylamide is added to 8.82 g of water and stirred for 15 min to fully dissolve the acrylamide prepolymer) is evenly sprayed on the wood fiber and mechanically stirred to obtain sizing wood fiber;
[0165] (7) Spray 0.1 mmol N,N'-methylenebisacrylamide and 0.027 mol ammonium persulfate solution onto the glued wood fiber and stir for 5 min to fully soak it;
[0166] (8) The glued wood fibers are pre-pressed into shape in a mold, and then hot-pressed on a flat vulcanizer (60° C., pressure 0.4 MPa, hot-pressing time 3 h) to obtain a flexible wood fiberboard through curing and cross-linking.
[0167] The flexible wood fiberboard prepared in the comparative example 3 was subjected to a single stretch-release cycle test under different strains and compared with that in the example 6. The results are as follows: Figure 8 It can be seen that when the non-isocyanate polyurethane content is 0, the maximum cyclic tensile stress of the prepared flexible wood fiberboard under different strains in a single stretch-release cycle is reduced by 92.92% compared with Example 6, and the strain is reduced to 20%, reflecting poor toughness.
[0168] The present invention provides a method for preparing a high-energy storage flexible wood fiber board and its application. First, a new conductive adhesive is prepared, and non-isocyanate polyurethane formed by the reaction of epoxy soybean oil cyclic carbonate and soybean protein is dispersed in the polyacrylamide macromolecular chain, and the hydrogen bond between the polyacrylamide chain and the non-isocyanate polyurethane is used to transmit external stress and dissipate energy, thereby improving the toughness of the adhesive; at the same time, a three-dimensional mesh structure formed by mixing porous wood fiber materials is used to introduce conductive materials to prepare conductive composite wood fibers, and a multi-dimensional-multi-scale hierarchical directional composite assembly technology of wood fiber materials and new conductive adhesives is used to achieve directional transmission of charges from polymers to wood channels, so that the flexible wood fiber board has the characteristic of intrinsic high energy storage. The present invention prepares a high-energy storage flexible wood fiber board through a new adhesive with high conductivity, which helps to solve the problem of the single carrier function of traditional furniture, provides a new solution for the realization of the integrated intelligent sustainable home of the Internet of Things, and helps to promote the high-value utilization of wood materials.
[0169] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a high energy storage flexible wood fiberboard, characterized in that: include, The epoxy soybean oil is mixed with tetrabutylammonium bromide, and the mixture is heated and pressurized to react with carbon dioxide to obtain the epoxy soybean oil cyclocarbonate; The soy protein powder is mixed with distilled water to obtain a mixed solution, and the mixed solution is subjected to a heating treatment to obtain a soy protein water dispersion; Epoxidized soybean oil-based cyclic carbonate is added to a soybean protein aqueous dispersion, the pH is adjusted to 10, and the mixture is heated for reaction to obtain a bio-based water-based non-isocyanate polyurethane; acrylamide and lithium chloride are added into the bio-based water-based non-isocyanate polyurethane, and fully dissolved to obtain a non-isocyanate polyurethane-acrylamide prepolymer; The conductive material is doped into the wood fiber and fully stirred to make it evenly dispersed to obtain a wood fiber mixture; The non-isocyanate polyurethane-acrylamide prepolymer is uniformly sprayed on the wood fiber mixture, and after being uniformly stirred, the sizing wood fiber is obtained; After N,N'-methylenebisacrylamide and ammonium persulfate are sprayed on the glued wood fiber, the fiber is pre-pressed in a mold, and then hot-pressed on a flat vulcanizer to cure and cross-link to obtain a high-energy storage flexible wood fiberboard.
2. The preparation method according to claim 1, characterized in that: The epoxy soybean oil and tetrabutylammonium bromide are mixed, wherein the mass ratio of the epoxy soybean oil to the tetrabutylammonium bromide is 1:0.01; the heating and pressurization are reacted with carbon dioxide, wherein the heating temperature is 130° C. and the pressure is 2.5 MPa.
3. The preparation method according to claim 1 or 2, characterized in that: The soy protein powder is mixed with distilled water to prepare a mixed solution, wherein the concentration of the soy protein in the mixed solution is 0.13-0.15 g / mL; the soy protein water dispersion is obtained by heating, wherein the heating temperature is 90-95° C. and the heating stirring time is 1.5-2 hours.
4. The preparation method according to claim 3, characterized in that: The epoxy soybean oil-based cyclic carbonate is added into the soybean protein water dispersion, wherein the mass ratio of the epoxy soybean oil-based cyclic carbonate to the soybean protein water dispersion is 1:3.3 to 1:3.
5.
5. The preparation method according to claim 1 or 4, characterized in that: The heating reaction obtains bio-based water-based non-isocyanate polyurethane, wherein the heating temperature is 80-85° C. and the reaction time is 0.5-1 h.
6. The preparation method according to claim 5, characterized in that: The acrylamide and lithium chloride are added to the bio-based water-based non-isocyanate polyurethane, wherein the mass ratio of acrylamide to the bio-based water-based non-isocyanate polyurethane is 1:0.85-1:0.87, and the mass ratio of lithium chloride to the bio-based water-based non-isocyanate polyurethane is 1:75-1:
77.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the conductive material to the wood fiber is 1:2; The mass ratio of the non-isocyanate polyurethane-acrylamide prepolymer to the wood fiber is 1:
1.
8. The preparation method according to claim 1 or 7, characterized in that: The amount of N,N'-methylenebisacrylamide added is 0.10-0.13% of the mass of acrylamide, and the amount of ammonium persulfate added is 4-5% of the mass of acrylamide; The hot pressing temperature is 60° C., the pressure is 0.4 MPa, and the hot pressing time is 3 hours.
9. A high energy storage flexible wood fiberboard prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the high energy storage flexible wood fiberboard according to claim 9 in smart furniture.
Citation Information
Patent Citations
Carbon fibre wood electromagnetic shielding material and preparation method thereof
CN103214865A
Fiber wood with electromagnetic shielding function and preparation method thereof
CN104985668A
Environment-friendly adhesive used for synthetic fiberboard and preparing method thereof
CN108943308A
Medium density fiberboard based on tannin-based cross-linking agent modified soybean meal adhesive and preparation method thereof
CN109849147A
Environment-friendly bio-based polyurethane adhesive and preparation method thereof
CN115305041A
Cited By
Bio-based non-isocyanate polyurethane wood adhesive as well as preparation method and application thereof
CN121718294A